Establishment Of Tissue Culture Planting Materials Of White Strawberry [Fragaria × Ananassa Var. Pearl White (Iroha-001)] For Indoor Fruit Farming With Led System - Pang, Wei Quan (2024)
This research investigates the multiple effects of variations in light spectrum and melatonin supplementation on the growth, development and genetic stability of in vitro-cultured Japanese Pearl White strawberry plants [Fragaria × ananassa var. Pearl White (Iroha-001)]. The Pearl White strawberry is a rare and exquisite fruit known for its striking appearance and unique flavour profile. Its luscious white colour and sweet, floral taste make it a coveted delicacy among fruit enthusiasts and connoisseurs. The white strawberry was chosen as a model plant because it is a high-quality, difficult-to-grow plant. Due to their low fruit yield, precise light treatment and labour-intensive cultivation, they are in high demand and therefore an ideal fruit for research. The study uses a comprehensive approach combining physiological, histological, and molecular analyses to elucidate the intricate interactions between these factors and their impact on tissue culture-based propagation. Surface sterilisation with a 30% Clorox solution (protocol 1) proved to be the most effective protocol, ensuring a clean and contamination-free starting point for the experiment. Subsequent studies revealed that the optimal medium for inducing multiple shoots and promoting proliferation involved the use of a 2 μM TDZ supplement in the Murashige and Skoog (MS) medium and without the need of auxins during root induction. The rooted plants successfully acclimatised to the ex vitro conditions and bore healthy fruit within a period of three months.